1982
DOI: 10.1111/j.1570-7458.1982.tb03145.x
|View full text |Cite
|
Sign up to set email alerts
|

LABORATORY EVALUATION OF CONTACT SEX PHEROMONE AND BISAZIR FOR AUTOSTERILIZATION OF GLOSSINA MORSITANS

Abstract: Using a combination of varying chemosterilant dose and exposure time, the ability of the compound bisazir, P, P‐bis (l‐aziridinyl)‐N‐methylphosphinothioic amide, to induce sterility in adult male G. m. morsitans has been evaluated by mating sterilized males to normal females and measuring their fecundity over 90 days. The product of dose and exposure time in hours is a constant for a given level of fertility reduction. The duration of copulatory responses of males to inanimate decoys dosed with G. m. morsitans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The effect that bisazir, at sterilizing doses in the vapour phase, has on tsetse behaviour, both the readiness to enter the sterilizing chamber and the speed of passage through it once inside is unknown. High doses of bisazir in the laboratory and in the field are irritating and even repellent to male G.m.morsitans when presented on pheromone-baited decoys (Coates & Langley, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The effect that bisazir, at sterilizing doses in the vapour phase, has on tsetse behaviour, both the readiness to enter the sterilizing chamber and the speed of passage through it once inside is unknown. High doses of bisazir in the laboratory and in the field are irritating and even repellent to male G.m.morsitans when presented on pheromone-baited decoys (Coates & Langley, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Decoys were 9 x 3-mm black-coloured, brushed nylon rectangles (Coates & Langley, 1982a), cleaned before use in ten changes of boiling chloroform. They were attached by their brushed sides with Velcro to a black cotton cloth screen of ca.…”
Section: General Field Conditionsmentioning
confidence: 99%
“…Initial field trials showed that males of G. m. morsitans responded to pheromone-baited decoys by alighting on them and attempting to mate (Langley et al, 1981), but the responses were short compared to those in the laboratory and occurred only with decoys attached to a moving screen. Coates & Langley (1982a) demonstrated that a combination of the sex pheromone and a chemosterilant, bisazir (P,P-bis(l-aziridinyl)-Ar-methylphosphinothioic amide), on a decoy could induce sterility in G. m. morsitans males. However, when such decoys were tested in the field with a view to developing an autosterilizing technique, most durations of contact between male and decoy were too short to be effective (Langley et al, 1982).…”
Section: Introductionmentioning
confidence: 99%